Time to viral load suppression in antiretroviral‐naive and ‐experienced HIV‐infected pregnant women on highly active antiretroviral therapy: implications for pregnant women presenting late in gestation1. Issue 12 (7th August 2013) - Aziz, N; Sokoloff, A; Kornak, J; Leva, NV; Mendiola, ML; Levison, J; Feakins, C; Shannon, M; Cohan, D
<x xml:space="preserve">Abstract</x> Objective To compare time to achieve viral load <400 copies/ml and <1000 copies/ml in HIV‐infected antiretroviral (ARV) ‐naive versus ARV‐experienced pregnant women on highly active antiretroviral therapy (HAART). Design Retrospective cohort study. Setting Three university medical centers, USA. Population HIV‐infected pregnant women initiated or restarted on HAART during pregnancy. Methods We calculated time to viral load <400 copies/ml and <1000 copies/ml in HIV‐infected pregnant women on HAART who reported at least 50% adherence, stratifying based on previous ARV exposure history. Main outcome measures Time to HIV viral load <400 copies/ml and <1000 copies/ml. Results We evaluated 138 HIV‐infected pregnant women, comprising 76 ARV‐naive and 62 ARV‐experienced. Ninety‐three percent of ARV‐naive women achieved a viral load < 400 copies/ml during pregnancy compared with 92% of ARV‐experienced women (P = 0.82). The median number of days to achieve a viral load < 400 copies/ml in the ARV‐naive cohort was 25.0 (range 3.5–133; interquartile range 16–34) days compared with 27.0 (range 8–162.5; interquartile range 18.5–54.3) days in the ARV‐experienced cohort (P = 0.02). In a multiple predictor analysis, women with higher adherence (adjusted relative hazard [aRH] per 10% increase in adherence 1.29, 95% confidence interval [CI] 1.08–1.54, P = 0.01) and receiving a non‐nucleotide reverse transcriptase inhibitor (NNRTI) ‐based regimen (aRH 2.48, 95% CI 1.33–4.63, P = 0.01) were more likely to achieve viral load <400 copies/ml earlier. Increased baseline HIV log10 viral load was associated with a later time of achieving viral load <400 copies/ml (aRH 0.60, 95% CI 0.39–0.92, P = 0.02). In a corresponding model of time to achieve viral load <1000 copies/ml, adherence (aRH per 10% increase in adherence 1.79, 95% CI 1.34–2.39, P < 0.001), receipt of NNRTI (aRH 2.95, 95% CI 1.23–7.06, P = 0.02), and CD4 cell count (aRH per 50 count increase in CD4 1.12, 95% CI 1.03–1.22, P = 0.01) were associated with an earlier time to achieve viral load below this threshold. Increasing baseline HIV log10 viral load was associated with a longer time of achieving viral load <1000 copies/ml (aRH 0.54, 95% CI 0.34–0.86, P = 0.01). In multiple predictor models, previous ARV exposure was not significantly associated with time to achieve viral load below thresholds of <400 copies/ml and <1000 copies/ml. Conclusions Pregnant women with ≥50% adherence, whether ARV‐naive or ARV‐experienced, on average achieve a viral load <400 copies/ml within a median of 26 days and a viral load of <1000 copies/ml within a median of 14 days of HAART initiation. Increased adherence, receipt of NNRTI‐based regimen and lower baseline HIV log10 viral load were all statistically significant predictors of earlier time to achieve viral load <400 copies/ml and <1000 copies/ml. Increased CD4 count was statistically significant as a predictor of earlier time to achieve viral load <1000 copies/ml.